Perceptions on socio-environmental conflicts in communities around the Biribiri State Park, Minas Gerais (Revista Espinhaço, 2018)
This research focuses on populations located in the Biribiri State Park buffer zone, Diamantina, Alto Vale do Jequitinhonha, Minas Gerais. It seeks to understand how the creation process of the Conservation Unit really took place, the social actors involved and changes brought to the surrounding population. For that purpose, a Management Plan was analyzed, as well as current environmental legislation and semi-structured interviews were conducted in order to investigate the possibility of socio-environmental conflicts between these populations and the protected area. The analysis of the socio-spatial context after implementation of the conservation unit allows to conclude that there is a great distance between communities and park, due to restrictions to the use of natural resources and to the territory.
Keywords: Upper Jequitinhonha; Conservation Unit; Traditional Communities; Buffer Zone